2020
DOI: 10.13171/mjc9602001101135ka
|View full text |Cite
|
Sign up to set email alerts
|

In vitro litholytic activity of extracts and phenolic fractions of some medicinal plants on urinary stones

Abstract: Objective: This study was carried out to evaluate the efficiency of plant extracts used in traditional medicine on the dissolution of oxalo-calcic and cystine stones. Also, the efficiency of phenolic fractions (Tannins and Flavonoids) for the plants that gave us the best stone dissolution rate. Subjects and methods: Kidney stone of oxalo-calcic and cystine stones were incubated in vitro for 8 weeks in the presence of five plants extracts (hydro-ethanolic and aqueous extracts). NaCl solution (0,9 %) use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…These findings are in agreement with those previously reported in different neighboring regions (Benarba et al, 2015;Bouasla and Bouasla, 2017;Chaachouay et al, 2020). Besides these species, Parietaria officinalis L. was found to possess an FL of 100% for kidney diseases which is consistent with findings previously reported in North-West Algeria (Benarba, 2016) and Morocco (Ammor et al, 2020). Inconsistent with our previous findings in both North-West (Benarba et al, 2015) and South-West Algeria (Benarba, 2016), T. vulgaris was the only species having the highest FL of 100% for skin diseases.…”
Section: Informant Consensus Factor and Flsupporting
confidence: 92%
“…These findings are in agreement with those previously reported in different neighboring regions (Benarba et al, 2015;Bouasla and Bouasla, 2017;Chaachouay et al, 2020). Besides these species, Parietaria officinalis L. was found to possess an FL of 100% for kidney diseases which is consistent with findings previously reported in North-West Algeria (Benarba, 2016) and Morocco (Ammor et al, 2020). Inconsistent with our previous findings in both North-West (Benarba et al, 2015) and South-West Algeria (Benarba, 2016), T. vulgaris was the only species having the highest FL of 100% for skin diseases.…”
Section: Informant Consensus Factor and Flsupporting
confidence: 92%
“…According to the traditional knowledge of the North-Eastern Moroccan population, this plant is considered a powerful and common medicinal herb that has shown significant results in treating kidney stones; renal colic; pyelonephritis; kidney pain; diuretic; detoxification of the kidneys; and polycystic kidney disease. From a pharmacological point of view, the aqueous extract of the aerial part of this plant has an inhibitory effect on the crystallization of calcium oxalate in vitro at doses of 0.0625 mg/mL and 0.5% of plant extracts in physiological solution (9 g of NaCl /L) [ 96 , 97 ], and in vivo at a concentration of 50 mg/mL [ 98 ], also has an effect on cystine stones in different patients with congenital cystinuria at a dose of 20 g/L [ 101 ]. Phytochemical studies have reported and identified some components of H. hirsuta include flavonoids, coumarin, tannins and saponins [ 100 , 171 , 172 , 173 ].…”
Section: Resultsmentioning
confidence: 99%
“…O. ficus-indica extract can reach a DR of 64 % and 45 % of the total mass of cystine stones and calcium oxalate stones, respectively. The DR of H. hirsute extracts gave 61 % for cystine stones, whereas it is 50 % when using calcium oxalate stones [16].…”
Section: Resultsmentioning
confidence: 87%